2010
DOI: 10.1016/j.yjmcc.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Normal passive viscoelasticity but abnormal myofibrillar force generation in human hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is characterized by left ventricular hypertrophy, increased ventricular stiffness and impaired diastolic filling. We investigated to what extent myocardial functional defects can be explained by alterations in the passive and active properties of human cardiac myofibrils. Skinned ventricular myocytes were prepared from patients with obstructive HCM (two patients with MYBPC3 mutations, one with a MYH7 mutation, and three with no mutation in either gene) and from four donors. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 32 publications
4
68
0
Order By: Relevance
“…These septal samples are characterized by a low level of phosphorylation of MyBP-C and troponin I (29,30,(55)(56)(57). In contrast, the two samples examined here, from free wall and from the atrial-septal junction region, showed high levels of phosphorylation similar to those in donor hearts (Fig.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 68%
“…These septal samples are characterized by a low level of phosphorylation of MyBP-C and troponin I (29,30,(55)(56)(57). In contrast, the two samples examined here, from free wall and from the atrial-septal junction region, showed high levels of phosphorylation similar to those in donor hearts (Fig.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 68%
“…Previous findings show that Myk461 inhibits myosin ATPase activity, decreases force generation, and prevents adverse cardiac remodeling in hypercontractile mouse hearts expressing HCM‐causing MHC missense mutations 21. It has been shown that myocardial samples isolated from HCM patients expressing cMyBPC mutations often display reduced total cMyBPC expression7, 25 and accelerated XB kinetics27; therefore, we sought to investigate the effects of Myk461 on the contractile function of myocardium lacking cMyBPC. In this context, recent data show that Myk461 stabilizes an autoinhibited state of 2‐headed myosin structure48 and also strengthens a folded‐back sequestered super‐relaxed state of myosin heads onto the thick filament backbone49—an effect that contributes to Myk461‐induced force depression by stabilizing the “ off ” state of myosin heads and preventing acto‐myosin formation.…”
Section: Discussionmentioning
confidence: 99%
“…The net result is decreased incorporation of full‐length cMyBPC into the sarcomere leading to haploinsufficiency 7, 8, 25, 26. Functionally, decreased incorporation of cMyBPC in human HCM samples expressing cMyBPC truncation mutations led to accelerated XB kinetics at submaximal Ca 2+ activations, in part, contributing to cardiac hypercontractility and hypertrophy 27. Mouse models of reduced cMyBPC expression or cMyBPC ablation also exhibit accelerated rates of XB recruitment and XB detachment rates at submaximal Ca 2+ activations,28, 29, 30 in part because reduced expression of cMyBPC radially displaces the myosin heads closer to actin, thereby effectively reducing the distance between actin and myosin and increasing the probability of acto‐myosin XB interactions 31.…”
Section: Introductionmentioning
confidence: 99%
“…Frozen samples of left ventricular myocardium from healthy unused donor hearts were obtained from the Sydney Heart Bank in Australia. The experimental set up and procedures were generally similar to those reported previously [23], except that the force measurements were made at a solution temperature of 37…”
Section: Methodsmentioning
confidence: 99%
“…Passive viscoelasticity was first measured using a series of five 1s step stretches with the myocyte in relaxing solution [23]. Resting sarcomere length (measured using Aurora HVSL.901A video analysis software at 200 Hz) was set to 1.95-2.05 µm in relaxing solution.…”
Section: Measurements Of Passive Viscoelasticitymentioning
confidence: 99%